Meta-Analisis Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Hasil Belajar Siswa Sekolah Dasar - I Made Hendra Sukmayasa (Edukasi: Jurnal Pendidikan Dasar, 2022)
This study aims to determine how much influence (effect size) type of Two Stay Two Stray cooperative learning model on learning outcomes of elementary school students. This type of research is a meta-analysis using data collection techniques in the form of library analysis of research that has been done previously. The data obtained were analyzed using quantitative descriptive data analysis. This analysis is used to analyze the effect size calculation data obtained from comparing the mean and standard deviation results of previous studies. Based on the results of the analysis, it can be concluded that the Two Stay Two Stray type of cooperative learning model in learning in elementary schools can be done in any region and in any subject. Testing the magnitude of the influence of the Two stay two stray cooperative learning model in learning in primary schools has an effect size in the high category, so that the Two stay two stray cooperative learning model is very feasible and supportive for learning in elementary schools.